Preparation method of thermochromic intelligent glass based on electrostatic spinning technology

The cerium oxide-vana dioxide composite nanoparticles were synthesized by the bi-in-situ hydrothermal method and the thermal color-changing composite nanofiber membrane was prepared using electrospinning technology, which solved the problem of poor thermal insulation effect of existing smart glasses in infrared and ultraviolet rays. It achieves high transmittance and excellent thermal discoloration performance, significantly improving UV resistance and aging resistance.

CN119116527AInactive Publication Date: 2024-12-13CHAOHU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411271567.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing smart glasses have poor thermal insulation effects in infrared and ultraviolet rays, and hot-color smart glasses based on electrospinning technology have not been reported, and lack of excellent thermal discoloration and UV resistance. Material.

Method used

The cerium oxide-vana dioxide composite nanoparticles were synthesized by di-in-situ hydrothermal method, and combined with polyvinyl alcohol through electrospinning technology, and cross-linked by glutaraldehyde to prepare the thermochromic composite nanofiber membrane as an interlayer of glass. Form smart glass with excellent thermal discoloration and UV resistance.

Benefits of technology

The prepared smart glass has high visible light transmittance and excellent thermal discoloration properties, and has good UV resistance and aging resistance, which is suitable for energy conservation and emission reduction needs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of thermochromic intelligent glass based on an electrostatic spinning technology. The preparation method comprises the following steps: synthesizing cerium oxide-vanadium dioxide composite nanoparticles through a double in-situ hydrothermal method; then, polyvinyl alcohol and the cerium oxide-vanadium dioxide composite nanoparticles are subjected to glutaraldehyde crosslinking through an electrostatic spinning technology, and a thermochromic composite nanofiber membrane is prepared; and finally, preparing the thermochromic intelligent glass by taking glass as a substrate. The method is simple in process and easy to industrialize; the prepared thermochromic intelligent glass not only has high visible light transmittance and excellent thermochromic performance, but also is good in ultraviolet resistance and aging resistance and good in effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a method for preparing thermochromic smart glass based on electrostatic spinning technology. Background Art

[0002] As greenhouse gas emissions become increasingly serious, energy conservation and emission reduction have gradually become the common development goals of all countries. Building energy consumption is particularly prominent, and glass materials account for 13% of the total building area, and heat dissipation reaches 70%. Among them, ordinary glass has poor insulation effect against infrared and ultraviolet rays.

[0003] Vanadium dioxide (VO2) is a transition metal oxide that undergoes a reversible insulating-metal phase transition at 68°C, from a semiconductor monoclinic phase (M phase) to a metallic state (R phase), and the optical properties undergo a sudden change along with the phase transition. At low temperatures, VO2 is in an insulating state with high infrared transmittance. At high temperatures, it is in a metallic state with low infrared transmittance, but the visible light transmittance remains almost unchanged. Therefore, VO2 can automatically adjust the heat generated by sunlight according to the temperature, and is an ideal intelligent energy-saving window material. At the same time, nano-cerium oxide is an excellent ultraviolet absorber, and its application in glass coatings can effectively improve the anti-ultraviolet and anti-aging properties.

[0004] At present, in the research and application of smart glass, vanadium dioxide is used and studied more, while nano cerium oxide is used and studied less, and thermochromic smart glass based on cerium oxide-vanadium dioxide-PVA film based on electrospinning technology has not been reported. Therefore, it is very necessary to develop a smart glass based on cerium oxide-vanadium dioxide-PVA film with excellent thermochromic performance and UV protection performance, which has very important practical value. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing thermochromic smart glass based on electrospinning technology, and the prepared smart glass has excellent thermochromic performance and anti-ultraviolet performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing thermochromic smart glass based on electrostatic spinning technology comprises the following steps:

[0008] S1, synthesizing cerium oxide-vanadium dioxide composite nanoparticles by dual in-situ hydrothermal method;

[0009] S2, preparing a thermochromic composite film from polyvinyl alcohol and cerium oxide-vanadium dioxide composite nanoparticles by electrospinning technology, and then cross-linking with glutaraldehyde to obtain a thermochromic composite nanofiber membrane;

[0010] S3. Thermochromic smart glass is prepared using glass as the substrate and thermochromic composite nanofiber membrane as the interlayer.

[0011] Preferably, the step S1 is specifically as follows:

[0012] S11. Preparation of cerium oxide precursor:

[0013] A certain amount of NaOH aqueous solution is measured and gradually added dropwise to a certain amount of Ce(NO3)36H2O aqueous solution under magnetic stirring to prepare a cerium oxide precursor;

[0014] S12, preparing vanadium dioxide precursor:

[0015] A certain amount of vanadium pentoxide, citric acid and deionized water are weighed and dissolved in a water bath, and then an activator is added. After mixing under magnetic stirring, a certain amount of NaOH aqueous solution is gradually added dropwise, and finally heated and cooled to room temperature to obtain a vanadium dioxide precursor.

[0016] S13, preparing nanocomposite particles:

[0017] A cerium oxide precursor and a vanadium dioxide precursor are placed in a high-pressure reactor, and then a dry SO2 gas flow is filled into the high-pressure reactor, and stirred at 80-90°C for 0.5-2h, and then allowed to stand at 300-500°C for 2-8h. After cooling, washing and drying, cerium oxide-vanadium dioxide nanocomposite particles with excellent thermochromic properties and UV protection properties are obtained.

[0018] Preferably, the step S2 is specifically as follows:

[0019] S21, measuring a certain amount of deionized water and polyvinyl alcohol, heating and dissolving them at 80-90° C. to obtain a polyvinyl alcohol aqueous solution, adding the prepared cerium oxide-vanadium dioxide composite nanoparticles, and continuing to stir at a constant temperature until mixed, to obtain a cerium oxide-vanadium dioxide-PVA aqueous solution;

[0020] S22, preparing a cerium oxide-vanadium dioxide-PVA film from a cerium oxide-vanadium dioxide-PVA aqueous solution by electrospinning technology, and then subjecting the film to a steam cross-linking reaction with a glutaraldehyde solution to obtain a cross-linked cerium oxide-vanadium dioxide-PVA film;

[0021] S23. Take a certain amount of deionized water and polyvinyl alcohol, heat and dissolve them at 80-90°C to obtain a polyvinyl alcohol treatment solution; then immerse the cerium oxide-vanadium dioxide-PVA membrane in the polyvinyl alcohol treatment solution, and finally obtain the thermochromic composite nanofiber membrane after drying.

[0022] Preferably, in the cerium oxide-vanadium dioxide-PVA aqueous solution, the concentration of polyvinyl alcohol is 5-10wt%, the concentration of cerium oxide-vanadium dioxide composite nanoparticles is 1-5wt%, and the concentration of polyvinyl alcohol in the polyvinyl alcohol treatment solution is 2-5wt%.

[0023] Preferably, the molar ratio of Ce in step S11 to vanadium pentoxide in step S12 is 100:(20-100).

[0024] Preferably, the S11 step is specifically as follows: measure a certain amount of Ce(NO3)36H2O and a certain amount of deionized water and place them in beaker A, and stir them magnetically for 10 minutes; then, in beaker B, measure a certain amount of NaOH and dissolve it in a certain amount of deionized water; finally, gradually drip the dissolved NaOH aqueous solution in beaker B into the Ce(NO3)36H2O aqueous solution in beaker A at a constant rate of 10-20mL / min, and stir beaker A magnetically at 70-80°C for 20-30 minutes, thereby obtaining a cerium oxide precursor.

[0025] Preferably, the molar ratio of Ce(NO3)36H2O to NaOH in beaker A is 1:3.

[0026] Preferably, in step S12, the activating agent is toluene, hexanol and hexadecyltrimethylammonium bromide.

[0027] Preferably, in step S12, the molar ratio of vanadium pentoxide to citric acid is 1:(2-5).

[0028] The beneficial effects of the present invention are:

[0029] The invention discloses a method for preparing thermochromic smart glass based on electrostatic spinning technology. Cerium oxide-vanadium dioxide composite nanoparticles are synthesized by a double in-situ hydrothermal method, and the process is simple and easy to industrialize. The prepared cerium oxide-vanadium dioxide composite nanoparticles are prepared by electrostatic spinning technology and cross-linking with glutaraldehyde to obtain a thermochromic composite nanofiber membrane. Finally, the thermochromic smart glass is prepared with glass as the substrate, which not only has high visible light transmittance and excellent thermochromic performance, but also has good anti-ultraviolet performance and aging resistance, and has a good effect. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the embodiments. It should be noted that these are merely examples and illustrations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should be deemed to fall within the protection scope of the present invention.

[0031] Embodiment 1:

[0032] A method for preparing thermochromic smart glass based on electrostatic spinning technology comprises the following steps:

[0033] S1. Synthesize cerium oxide-vanadium dioxide composite nanoparticles using a dual in-situ hydrothermal method.

[0034] S11, preparing cerium oxide precursor:

[0035] 0.1 mol of Ce(NO3)36H2O and a certain amount of deionized water were placed in beaker A, and magnetically stirred for 10 minutes to mix well. Then, in beaker B, 0.3 mol of NaOH was dissolved in a certain amount of deionized water, and stirred to form a NaOH aqueous solution.

[0036] Finally, the dissolved NaOH aqueous solution in beaker B was gradually dripped into the Ce(NO3)36H2O aqueous solution in beaker A at a constant rate of 10 mL / min, and beaker A was magnetically stirred at 70°C for 30 min to obtain a cerium oxide precursor.

[0037] S12, preparing vanadium dioxide precursor:

[0038] 0.02 mol of vanadium pentoxide, 0.04 mol of citric acid and 50 ml of deionized water were measured and stirred in a water bath at 80°C until they were completely dissolved. Then, active agents such as toluene, hexanol and hexadecyltrimethylammonium bromide were added. After mixing under magnetic stirring, a certain amount of NaOH aqueous solution was gradually added dropwise to make the solution neutral. Finally, the mixed solution was heated to 100°C for 2 hours and then cooled to room temperature to obtain a vanadium dioxide precursor.

[0039] S13, preparing nanocomposite particles:

[0040] A cerium oxide precursor and a vanadium dioxide precursor are placed in a high-pressure reactor, and then a dry SO2 gas flow is introduced into the high-pressure reactor. The mixture is stirred at 80°C for 2 hours, and then allowed to stand at 300°C for 8 hours. After cooling, washing and drying, cerium oxide-vanadium dioxide nanocomposite particles with excellent thermochromic properties and UV protection properties are obtained.

[0041] S2. Polyvinyl alcohol and cerium oxide-vanadium dioxide composite nanoparticles are prepared by electrospinning technology to form a thermochromic composite film, which is then cross-linked by glutaraldehyde to obtain a thermochromic composite nanofiber membrane, as follows:

[0042] S21, measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve at 80 ° C to obtain a polyvinyl alcohol aqueous solution, then add the prepared cerium oxide-vanadium dioxide composite nanoparticles, continue to stir at a constant temperature until mixed, and obtain a cerium oxide-vanadium dioxide-PVA aqueous solution. Wherein, in the cerium oxide-vanadium dioxide-PVA aqueous solution, the concentration of polyvinyl alcohol is 5wt%, and the concentration of cerium oxide-vanadium dioxide composite nanoparticles is 5wt%.

[0043] S22, preparing a cerium oxide-vanadium dioxide-PVA film from a cerium oxide-vanadium dioxide-PVA aqueous solution by electrostatic spinning technology, and then subjecting the film to a cross-linking reaction with steam of a glutaraldehyde solution to obtain a cross-linked cerium oxide-vanadium dioxide-PVA film, wherein the concentration of the glutaraldehyde solution is 7wt%.

[0044] S23. Measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve them at 80-90°C to obtain a polyvinyl alcohol treatment solution, wherein the concentration of polyvinyl alcohol is 5wt%; then immerse the cerium oxide-vanadium dioxide-PVA membrane in the polyvinyl alcohol treatment solution, and finally obtain the thermochromic composite nanofiber membrane after drying.

[0045] S3. Thermochromic smart glass is prepared using glass as the substrate and thermochromic composite nanofiber membrane as the interlayer.

[0046] The prepared thermochromic smart glass is three-layer, including two layers of base glass and one layer of thermochromic composite nanofiber membrane. The three-layer smart glass was tested and its phase transition temperature was 41°C, visible light transmittance was 76.6%, and ultraviolet light transmittance was 17.6%.

[0047] Embodiment 2:

[0048] A method for preparing thermochromic smart glass based on electrostatic spinning technology comprises the following steps:

[0049] S1. Synthesize cerium oxide-vanadium dioxide composite nanoparticles using a dual in-situ hydrothermal method.

[0050] S11. Preparation of cerium oxide precursor:

[0051] 0.1 mol of Ce(NO3)36H2O and a certain amount of deionized water were placed in beaker A, and magnetically stirred for 10 minutes to mix well. Then, in beaker B, 0.3 mol of NaOH was dissolved in a certain amount of deionized water, and stirred to form a NaOH aqueous solution.

[0052] Finally, the dissolved NaOH aqueous solution in beaker B was gradually dripped into the Ce(NO3)36H2O aqueous solution in beaker A at a constant rate of 20 mL / min, and beaker A was magnetically stirred at 80°C for 20 min to obtain a cerium oxide precursor.

[0053] S12, preparing vanadium dioxide precursor:

[0054] 0.1 mol of vanadium pentoxide, 0.3 mol of citric acid and 100 ml of deionized water were measured and stirred in a 70°C water bath until completely dissolved. Then, active agents such as toluene, hexanol and hexadecyltrimethylammonium bromide were added. After mixing under magnetic stirring, a certain amount of NaOH aqueous solution was gradually added dropwise to make the solution neutral. Finally, the mixed solution was heated to 100°C for 2 hours and then cooled to room temperature to obtain a vanadium dioxide precursor.

[0055] S13, preparing nanocomposite particles:

[0056] A cerium oxide precursor and a vanadium dioxide precursor are placed in a high-pressure reactor, and then a dry SO2 gas flow is introduced into the high-pressure reactor. The mixture is stirred at 90°C for 0.5h, and then allowed to stand at 500°C for 2h. After cooling, washing and drying, cerium oxide-vanadium dioxide nanocomposite particles with excellent thermochromic properties and UV protection properties are obtained.

[0057] S2. Polyvinyl alcohol and cerium oxide-vanadium dioxide composite nanoparticles are prepared by electrospinning technology to form a thermochromic composite film, which is then cross-linked by glutaraldehyde to obtain a thermochromic composite nanofiber membrane, as follows:

[0058] S21, measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve at 90 ° C to obtain a polyvinyl alcohol aqueous solution, then add the prepared cerium oxide-vanadium dioxide composite nanoparticles, continue to stir at a constant temperature until mixed, and obtain a cerium oxide-vanadium dioxide-PVA aqueous solution. Wherein, in the cerium oxide-vanadium dioxide-PVA aqueous solution, the concentration of polyvinyl alcohol is 10wt%, and the concentration of cerium oxide-vanadium dioxide composite nanoparticles is 1wt%.

[0059] S22, preparing a cerium oxide-vanadium dioxide-PVA film from a cerium oxide-vanadium dioxide-PVA aqueous solution by electrostatic spinning technology, and then subjecting the film to a cross-linking reaction with steam of a glutaraldehyde solution to obtain a cross-linked cerium oxide-vanadium dioxide-PVA film, wherein the concentration of the glutaraldehyde solution is 15wt%.

[0060] S23. Measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve them at 80-90°C to obtain a polyvinyl alcohol treatment solution, wherein the concentration of polyvinyl alcohol is 2wt%; then immerse the cerium oxide-vanadium dioxide-PVA membrane in the polyvinyl alcohol treatment solution, and finally obtain the thermochromic composite nanofiber membrane after drying.

[0061] S3. Thermochromic smart glass is prepared using glass as the substrate and thermochromic composite nanofiber membrane as the interlayer.

[0062] The prepared thermochromic smart glass has five layers, including three layers of base glass and two layers of thermochromic composite nanofiber membrane, and the base glass and the thermochromic composite nanofiber membrane are arranged alternately. The five-layer smart glass was tested and its phase change temperature was 43°C, the visible light transmittance was 62.7%, and the ultraviolet light transmittance was 3.6%.

[0063] Embodiment 3:

[0064] A method for preparing thermochromic smart glass based on electrostatic spinning technology comprises the following steps:

[0065] S1. Synthesize cerium oxide-vanadium dioxide composite nanoparticles using a dual in-situ hydrothermal method.

[0066] S11. Preparation of cerium oxide precursor:

[0067] 0.1 mol of Ce(NO3)36H2O and a certain amount of deionized water were placed in beaker A, and magnetically stirred for 10 minutes to mix well. Then, in beaker B, 0.3 mol of NaOH was dissolved in a certain amount of deionized water, and stirred to form a NaOH aqueous solution.

[0068] Finally, the dissolved NaOH aqueous solution in beaker B was gradually dripped into the Ce(NO3)36H2O aqueous solution in beaker A at a constant rate of 10-20 mL / min, and beaker A was magnetically stirred at 75°C for 25 minutes to obtain a cerium oxide precursor.

[0069] S12, preparing vanadium dioxide precursor:

[0070] Measure 0.06 mol of vanadium pentoxide, 0.12 mol of citric acid, and 150 ml of deionized water, stir and dissolve completely in a 75°C water bath, then add activating agents toluene, hexanol, and hexadecyltrimethylammonium bromide, mix under magnetic stirring, and gradually add a certain amount of NaOH aqueous solution to make the solution neutral; finally, heat the mixed solution to 100°C for 2 hours, and then cool to room temperature to obtain a vanadium dioxide precursor.

[0071] S13, preparing nanocomposite particles:

[0072] A cerium oxide precursor and a vanadium dioxide precursor are placed in a high-pressure reactor, and then a dry SO2 gas flow is introduced into the high-pressure reactor. The mixture is stirred at 85°C for 1 hour, and then allowed to stand at 400°C for 5 hours. After cooling, washing and drying, cerium oxide-vanadium dioxide nanocomposite particles with excellent thermochromic properties and UV protection properties are obtained.

[0073] S2. Polyvinyl alcohol and cerium oxide-vanadium dioxide composite nanoparticles are prepared by electrospinning technology to form a thermochromic composite film, which is then cross-linked by glutaraldehyde to obtain a thermochromic composite nanofiber membrane, as follows:

[0074] S21, measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve at 85 ° C to obtain a polyvinyl alcohol aqueous solution, then add the prepared cerium oxide-vanadium dioxide composite nanoparticles, continue to stir at a constant temperature until mixed, and obtain a cerium oxide-vanadium dioxide-PVA aqueous solution. Wherein, in the cerium oxide-vanadium dioxide-PVA aqueous solution, the concentration of polyvinyl alcohol is 7.5wt%, and the concentration of cerium oxide-vanadium dioxide composite nanoparticles is 3wt%.

[0075] S22, preparing a cerium oxide-vanadium dioxide-PVA film from a cerium oxide-vanadium dioxide-PVA aqueous solution by electrostatic spinning technology, and then subjecting the film to a cross-linking reaction with steam of a glutaraldehyde solution to obtain a cross-linked cerium oxide-vanadium dioxide-PVA film, wherein the concentration of the glutaraldehyde solution is 10wt%.

[0076] S23. Measure a certain amount of deionized water and polyvinyl alcohol, heat and dissolve them at 80-90°C to obtain a polyvinyl alcohol treatment solution, wherein the concentration of polyvinyl alcohol is 3.5wt%; then immerse the cerium oxide-vanadium dioxide-PVA membrane in the polyvinyl alcohol treatment solution, and finally obtain the thermochromic composite nanofiber membrane after drying.

[0077] S3. Thermochromic smart glass is prepared using glass as the substrate and thermochromic composite nanofiber membrane as the interlayer.

[0078] The prepared thermochromic smart glass is three-layer, including two layers of base glass and one layer of thermochromic composite nanofiber membrane. The three-layer smart glass was tested and its phase transition temperature was 40°C, visible light transmittance was 79.6%, and ultraviolet light transmittance was 17.3%.

[0079] It can be seen from Example 1, Example 2, and Example 3 that the phase change temperature of the thermochromic smart glass prepared by the method for preparing thermochromic smart glass based on electrospinning technology of the present invention is about 40°C. The three-layer thermochromic smart glass prepared by Example 1 and Example 3 has a visible light transmittance of more than 78% and an ultraviolet light transmittance of less than 18%. The five-layer thermochromic smart glass prepared in Example 2 has a visible light transmittance of 62.7% and an ultraviolet light transmittance of 3.6% due to the double-layer thermochromic composite nanofiber membrane used. With one more layer of thermochromic composite nanofiber membrane, its visible light transmittance and ultraviolet light transmittance are greatly reduced, but the process cost is relatively high.

[0080] The invention discloses a method for preparing thermochromic smart glass based on electrostatic spinning technology. Cerium oxide-vanadium dioxide composite nanoparticles are synthesized by a double in-situ hydrothermal method, and the process is simple and easy to industrialize. The prepared cerium oxide-vanadium dioxide composite nanoparticles are prepared by electrostatic spinning technology and cross-linking with glutaraldehyde to obtain a thermochromic composite nanofiber membrane. Finally, the thermochromic smart glass is prepared with glass as the substrate, which not only has high visible light transmittance and excellent thermochromic performance, but also has good anti-ultraviolet performance and aging resistance, and has a good effect.

[0081] The above is an exemplary description of the invention. Obviously, the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for preparing thermochromic smart glass based on electrospinning technology, characterized in that: The steps include: S1, synthesizing cerium oxide-vanadium dioxide composite nanoparticles by dual in-situ hydrothermal method; S2, preparing a thermochromic composite film from polyvinyl alcohol and cerium oxide-vanadium dioxide composite nanoparticles by electrospinning technology, and then cross-linking with glutaraldehyde to obtain a thermochromic composite nanofiber membrane; S3. Thermochromic smart glass is prepared using glass as the substrate and thermochromic composite nanofiber membrane as the interlayer.

2. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 1, characterized in that: The S1 step is specifically as follows: S11, preparing cerium oxide precursor: A certain amount of NaOH aqueous solution is measured and gradually added dropwise to a certain amount of Ce(NO3)36H2O aqueous solution under magnetic stirring to prepare a cerium oxide precursor; S12, preparing vanadium dioxide precursor: A certain amount of vanadium pentoxide, citric acid and deionized water are weighed and dissolved in a water bath, and then an activator is added. After mixing under magnetic stirring, a certain amount of NaOH aqueous solution is gradually added dropwise, and finally heated and cooled to room temperature to obtain a vanadium dioxide precursor. S13, preparing nanocomposite particles: A cerium oxide precursor and a vanadium dioxide precursor are placed in a high-pressure reactor, and then a dry SO2 gas flow is filled into the high-pressure reactor, and stirred at 80-90°C for 0.5-2h, and then allowed to stand at 300-500°C for 2-8h. After cooling, washing and drying, cerium oxide-vanadium dioxide nanocomposite particles with excellent thermochromic properties and UV protection properties are obtained.

3. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 1, characterized in that: The S2 step is specifically as follows: S21, measuring a certain amount of deionized water and polyvinyl alcohol, heating and dissolving them at 80-90° C. to obtain a polyvinyl alcohol aqueous solution, adding the prepared cerium oxide-vanadium dioxide composite nanoparticles, and continuing to stir at a constant temperature until mixed, to obtain a cerium oxide-vanadium dioxide-PVA aqueous solution; S22, preparing a cerium oxide-vanadium dioxide-PVA film from a cerium oxide-vanadium dioxide-PVA aqueous solution by electrospinning technology, and then subjecting the film to a steam cross-linking reaction with a glutaraldehyde solution to obtain a cross-linked cerium oxide-vanadium dioxide-PVA film; S23. Take a certain amount of deionized water and polyvinyl alcohol, heat and dissolve them at 80-90°C to obtain a polyvinyl alcohol treatment solution; then immerse the cerium oxide-vanadium dioxide-PVA membrane in the polyvinyl alcohol treatment solution, and finally obtain the thermochromic composite nanofiber membrane after drying.

4. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 3, characterized in that: In the cerium oxide-vanadium dioxide-PVA aqueous solution, the concentration of polyvinyl alcohol is 5-10wt%, the concentration of cerium oxide-vanadium dioxide composite nanoparticles is 1-5wt%, and the concentration of polyvinyl alcohol in the polyvinyl alcohol treatment solution is 2-5wt%.

5. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 2, characterized in that: The molar ratio of Ce in step S11 to vanadium pentoxide in step S12 is 100:(20-100).

6. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 2, characterized in that: The S11 step is specifically as follows: A certain amount of Ce(NO3)36H2O and a certain amount of deionized water are measured and placed in beaker A, and magnetically stirred for 10 minutes; then, in beaker B, a certain amount of NaOH is measured and dissolved in a certain amount of deionized water; finally, the dissolved NaOH aqueous solution in beaker B is gradually dripped into the Ce(NO3)36H2O aqueous solution in beaker A at a constant rate of 10-20mL / min, and beaker A is magnetically stirred at 70-80°C for 20-30 minutes, thereby obtaining a cerium oxide precursor.

7. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 6, characterized in that: The molar ratio of Ce(NO3)36H2O to NaOH in beaker A is 1:

3.

8. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 2, characterized in that: In step S12, the activating agent is toluene, hexanol and hexadecyltrimethylammonium bromide.

9. The method for preparing thermochromic smart glass based on electrospinning technology according to claim 2, characterized in that: In step S12, the molar ratio of vanadium pentoxide to citric acid is 1:(2-5).

Citation Information

Patent Citations

  • Production method of durable anti-ultraviolet chinlon 6 fiber

    CN102433602A

  • Preparation method for cerium dioxide nanobelts or cerium dioxide nanotubes

    CN104261456A

  • Method for preparing transparent VO2 heat color intelligent thin film through electrospinning technique

    CN106978671A

  • Method for preparing hydrophobic transparent vanadium dioxide thermochromic smart glass by electrospinning technology

    CN108164154A